Static flexure of thick orthotropic plates using trigonometric shear deformation theory - Ghugal, Yuwaraj M.; Sayyad, Atteshamuddin S. (Journal of Structural Engineering, 2024)
A trigonometric shear deformation theory taking into account transverse shear deformation effect as well as transverse normal strain effect is presented for the flexural analysis of thick orthotropic plates. The inplane displacement field uses sinusoidal function in terms of thickness coordinate to include the shear deformation effect. The cosine function in thickness coordinates is used in transverse displacement to include the effect of transverse normal strain. The theory obviates the need of shear correction factor. Governing equations and boundary conditions of the theory are obtained using the principle of virtual work. Results obtained for static flexure of simply supported orthotropic plates with various loading cases are compared with those of other refined theories and elasticity solution wherever applicable.